Gathering at Silver Glen : community and history in late archaic Florida - Gilmore, Zackary I. (Florida Museum of Natural History. Ripley P. Bullen series, 2017)
Broadening our understanding of southeastern hunter-gatherers who lived between 4600 and 3500 BC, Zackary Gilmore presents evidence that the Late Archaic community of Silver Glen - one of Florida's most elaborate shell mound complexes - integrated people and places from throughout Florida by staging large-scale feasts and other public events.